Species And Genotypic Diversity Of Non-Tuberculous Mycobacteria Isolated From Children Investigated For Pulmonary Tuberculosis In Rural Uganda - Asiimwe, Benon B.; Bagyenzi, Godwins B.; Ssengooba, Willy; Mumbowa, Francis; Mboowa, Gerald; Wajja, Anne; Kiiza, Harriet Mayanja; Musoke, Philippa M.; Wobudeya, Eric; Kallenius, Gunilla; Joloba, Moses L. (BMC infectious diseases, 2013)
Smear microscopy, a mainstay of tuberculosis (TB) diagnosis in developing countries, cannot differentiate M. tuberculosis complex from NTM infection, while pulmonary TB shares clinical signs with NTM disease, causing clinical and diagnostic dilemmas. This study used molecular assays to identify species and assess genotypic diversity of non-tuberculous mycobacteria (NTM) isolates from children investigated for pulmonary tuberculosis at a demographic surveillance site in rural eastern Uganda. Children were investigated for pulmonary tuberculosis as part of a TB vaccine surveillance program (2009–2011). Two cohorts of 2500 BCG vaccinated infants and 7000 adolescents (12–18 years) were recruited and followed up for one to two years to determine incidence of tuberculosis. Induced sputum and gastric aspirates were processed by the standard N-acetyl L-cysteine (NALC)-NaOH method. Sediments were cultured in the automated MGIT (Becton Dickson) liquid culture system and incubated at 37°C for at least six weeks. Capilia TB assay was used to classify mycobacteria into MTC and NTM. The GenoType CM/AS assays were performed to identify species while Enterobacterial Repetitive Intergenic Consensus (ERIC) PCR genotyping was used to assess genetic diversity of the strains within each species. Among 2859 infants and 2988 adolescents screened, the numbers of TB suspects were 710 and 1490 infants and adolescents respectively. The prevalence of NTM in infant suspects was 3.7% (26/710) (95% CI 2.5–5.2) while that in adolescent suspects was 4.6% (69/1490) (95% CI 3.6–5.8). On culture, 127 isolates were obtained, 103 of which were confirmed as mycobacteria comprising of 95 NTM and eight M. tuberculosis complex. The Genotype CM/AS assay identified 63 of the 95 NTM isolates while 32 remained un-identified. The identified NTM species were M. fortuitum (40 isolates, 63.5%), M. szulgai (9 isolates, 14.3%), M. gordonae (6 isolates, 9.5%), M. intracellulare (3 isolates, 4.7%), M. scrofulaceum (2 isolates, 3.2%), M. lentiflavum (2 isolates, 3.2%), and M. peregrinum (1 isolate, 1.6%). Genotyping did not reveal any clustering in M. intracellulare, M. gordonae and M. szulgai species. M. fortuitum, on the other hand, had two clusters, one with three isolates of M. fortuitum 1 and the other with two isolates of M. fortuitum 2 subspecies. The remaining 35 of the 40 isolates of M. fortuitum had unique fingerprint patterns.M. fortuitum is the most common cause of infection by NTM among Infants and adolescents in rural Uganda. There is a varied number of species and genotypes, with minimal clustering within species, suggesting ubiquitous sources of infection to individuals in this community.
Keywords: Pulmonary Tuberculosis; Tuberculosis Complex; SmearMicroscopy; Enterobacterial Repetitive Intergenic Consensus; Demographic Surveillance Site